2016
DOI: 10.3389/fmicb.2016.00896
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biocide Mitigation of Field Biofilm Consortia by a Mixture of D-Amino Acids

Abstract: Microbiologically influenced corrosion (MIC) is a major problem in the oil and gas industry as well as in many other industries. Current treatment methods rely mostly on pigging and biocide dosing. Biocide resistance is a growing concern. Thus, it is desirable to use biocide enhancers to improve the efficacy of existing biocides. D-Amino acids are naturally occurring. Our previous work demonstrated that some D-amino acids are biocide enhancers. Under a biocide stress of 50 ppm (w/w) hydroxymethyl phosphonium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 36 publications
2
43
0
2
Order By: Relevance
“…Effects of D-amino acids on B. subtilis may be simply due to toxic effects of inhibition of protein synthesis (48). Others have reported that mixtures of D-amino acids (49) or combinations of D-amino acids with antibiotics (50) may be more effective against biofilm formation than individual D-amino acids. Interpretation of these studies is complicated due to differences in strains, biofilm assays (for example, microtiter plate vs. flow-cell), and the dosage of specific D-amino acids used (51).…”
Section: Introductionmentioning
confidence: 99%
“…Effects of D-amino acids on B. subtilis may be simply due to toxic effects of inhibition of protein synthesis (48). Others have reported that mixtures of D-amino acids (49) or combinations of D-amino acids with antibiotics (50) may be more effective against biofilm formation than individual D-amino acids. Interpretation of these studies is complicated due to differences in strains, biofilm assays (for example, microtiter plate vs. flow-cell), and the dosage of specific D-amino acids used (51).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, DAAs were shown to augment the action of two additional industrial biocides against a biofilm consortium of sulfate reducing bacteria. The application of a DAAs cocktail that was previously optimized for B. subtilis [9] together with THPS reduced by a three to four order of magnitudes the biofilm cell counts compared with THPS alone, depending on the consortia composition [28]. Strikingly, just as in the original study [9], a mix of DAAs was extremely efficient in dispersing biofilm consortia, while the i ndividual DAAs were less potent [28].…”
mentioning
confidence: 83%
“…Chloride, glutaraldehyde and quaternary ammonium compounds are the biocides most widely used in the control of biocorrosion [9][10][11] . However, sessile cells are very difficult to mitigate because of their diffusional barrier (which slows down the penetration of biocides), intentionally low metabolic rate (which reduces the biocide intake), preservation of persistent cells, upregulation of resistance genes that code for proteins that degrade antimicrobials and presence of efflux pumps to remove harmful chemicals 6,12 . Therefore, due to the various defense mechanisms employed by biofilms, high dosages of biocides must be used in field applications to eliminate the sessile cells.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the use of alternative, environmentally friendly biocides is of great industrial interest. Currently, tetrakishydroxymethylphosphonium sulfate (THPS) is the green biocide generally used in the oil and gas industries 4 , either alone or in mixtures with aminoacids 6,12,16 . Recently, glyceryl trinitrate (GTN) and caprylic acid (CA), two biodegradable biocides with potential for field applications, were also evaluated for mitigation of D. vulgaris biofilms on C1018 carbon steel coupons 17 .…”
Section: Introductionmentioning
confidence: 99%